Women’s Contribution to Sustainable Development on Patipata (Schumannianthus dichotoma) Based Cottage Industries in Sylhet Region, Bangladesh - Haque, Israt Eshita; Hossain, Md. Sabbir (Technium Social Sciences Journal, 2021)
The role of women in sustainable development is very crucial in society. This study was intended to investigate women’s contribution to sustainable development on patipata based cottage industries evaluating its productivity & profitability and also mentioning challenges & further recommendations at Angarzur village of Gowainghat Upazilla in Sylhet region, Bangladesh. The study area and 125 respondents were selected by purposive sampling because of its nature and subject matter in where survey research was carried out with a semi-structured questionnaire. Middle aged female are highly involved in patipata-based cottage industries in this area. Women produce different types of patipata-based articles that require 2- 7 days from where women earn annually about 77,965/=Tk. Women play a major part in the production process and around 333 numbers of articles are sold per year. For different types of articles, the net average cost ranges from 45 Tk. to 270 Tk. and net average profit ranges from 30 Tk. to 410 Tk. The demand of patipata based articles has found a significant distinction in rural-urban areas. However, the sustainability of women’s contribution to this business faces some challenges that should be reduced through the collaboration of concerned authorities.